Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1007/s10639-022-10938-4
|View full text |Cite|
|
Sign up to set email alerts
|

“In the shoes of another”: immersive technology for social and emotional learning

Abstract: There has been increasing use of interactive technologies in the classroom today and a rising popularity of employing virtual environments as a means to engage students in sensorially rich contexts for more embodied forms of experiential learning. In particular, virtual reality (VR) or immersive virtual environments (IVEs) facilitated by head-mounted displays (HMDs) have been used in the teaching of subject content such as history, geography and science. This article presents the findings of an exploratory stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Our findings contribute to the growing body of evidence that supports the efficacy of immersive VR experiences in enhancing empathy. Several earlier studies have demonstrated that VR can effectively simulate real-world scenarios, enabling participants to step into the shoes of others and experience situations from different perspectives (Dwivedi et al, 2022;Tan et al, 2022). Such immersive experiences can foster a deeper understanding of patients' emotions and perspectives, a cornerstone of empathy (Bailenson, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings contribute to the growing body of evidence that supports the efficacy of immersive VR experiences in enhancing empathy. Several earlier studies have demonstrated that VR can effectively simulate real-world scenarios, enabling participants to step into the shoes of others and experience situations from different perspectives (Dwivedi et al, 2022;Tan et al, 2022). Such immersive experiences can foster a deeper understanding of patients' emotions and perspectives, a cornerstone of empathy (Bailenson, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…On this basis, attitude requires that students perceive that the knowledge to be obtained is (i) significant and useful ( perceived usefulness ). In order to achieve this, different studies show the need to previously increase students’ emotional engagement and motivation by means of techniques that foment empathy and self-reflection (Tan et al, 2022 ), and the capacity to resolve and channel the possible conflicts that could arise amongst students (Schnaubert & Bodemer, 2019 ). In the specific literature, Boateng et al ( 2016 ) used data collected from a questionnaire administered to 337 students at the University of Ghana to support the idea that perceived usefulness has a direct relation with attitude in respect to the use of new technologies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Meanwhile, VR has proven useful in training the classroom management ability of pre-service teachers [18,19]. Additionally, some evidence finds that this technology is not necessarily more effective than pen and paper and video viewing approaches for learn socio-emotional competences in teenagers [20]. Another review indicates that mixed-reality simulation in particular has the potential for contributing to teacher education, because it offers the potential for learning in various contexts when compared to traditional didactic teaching practices [21].…”
Section: Literature Reviewmentioning
confidence: 99%